Preventing Stunting by Utilizing Catfish Farming to Produce Catfish Nugget Food in Pengempon Village - Alam, Fitrah Pesona; Sholehah, Afidah Nur; Saputra, Ageng Adi; Utami, Liza Tri; Ferdiantoro, Andika; Ramadanti, Devinda Nuzrul; Oktavia, Nengsih; Anastasia, Fikenza Aura; Wibowo, Syaka Athallya Varizqi; Aulia, Nadia Rizqi; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
This community service program aimed to prevent stunting in Pengempon Village, Kebumen Regency, through education and training on processing catfish into nutritious nuggets. Stunting, a chronic malnutrition condition, remains a public health concern in Indonesia despite recent prevalence reductions. The program applied a Participatory Action Research (PAR) approach, involving 44 members of the local PKK women’s group. Activities included stunting prevention education and hands-on catfish nugget production. Pretest–posttest evaluations showed a total score increase of 380 points, indicating improved knowledge about stunting causes, impacts, and prevention strategies. Catfish, chosen for its high protein and low mercury content, was processed into nuggets to enhance its appeal, especially to children. This approach not only addressed nutritional gaps but also introduced potential for local economic development through small-scale production. The program demonstrated that combining nutrition education with practical food processing can effectively improve community awareness and promote healthier dietary habits.